2011
DOI: 10.1002/ppul.21512
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐reported ISAAC written questionnaire may underestimate the prevalence of asthma in children aged 10–12 years

Abstract: The ISAAC AVQ may be another effective instrument for assessing the prevalence of asthma symptoms in children aged 10-12 years, whereas the parent-reported-WQ may underestimate the prevalence of asthma symptoms in this age-group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
5
11
0
Order By: Relevance
“…These results demonstrate that the questionnaire is a useful tool to exclude atopic diseases but has strong limitations in confirming an existing allergy. Low sensitivity rates found in both groups make us question the reliability of questionnaires . Our results are in line with Caffarelli et al who investigated 63 patients with T1D and 108 controls .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results demonstrate that the questionnaire is a useful tool to exclude atopic diseases but has strong limitations in confirming an existing allergy. Low sensitivity rates found in both groups make us question the reliability of questionnaires . Our results are in line with Caffarelli et al who investigated 63 patients with T1D and 108 controls .…”
Section: Discussionsupporting
confidence: 91%
“…The vast majority of studies conducted so far define allergic disease by patient‐reported allergic symptoms in questionnaires. However, self‐awareness of allergic symptoms has been shown to be biased and inaccurate . In only a few studies allergy tests, such as a skin prick test or measurement of allergen‐specific serum IgE antibodies (by ImmunoCAP), were performed.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline questionnaires were obtained on enrollment and included questions on the presence and source of allergies. The questionnaire used is not validated and not age‐specific; caregivers routinely completed questionnaires for children <18 years of age, which may underestimate the prevalence of allergies as suggested from the asthma literature 20–22. Subjects were excluded from analyses if complete questionnaire data were not available, which yielded a study sample of 1,321 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…However, the recently performed nonresponder analyses in the Swedish [18] and the Norwegian [19] studies indicate that our results are fairly valid. To further complicate the discussion, the estimation of asthma prevalence through ISAAC questionnaires answered by the children's parents may not always correlate with the actual prevalence, as the parents may not be aware of or observe the children's respiratory symptoms [20], leading to an underestimation of asthma prevalence.…”
Section: Discussionmentioning
confidence: 99%